Biological aspects of Curinus sp., a predator of scale of "palma forrageira" - Lima, Cleonor Cavalcante Alves de; Barbosa, Sérgio Mauro de Lima (Pesquisa Agropecuaria Brasileira, 2014)
This work describes some aspects of biology of Curinus sp. (Coleoptera, Coccinellidae) a predator of Diaspis echinocacti (Bouché, 1833) which is a serious pest of "palma forrageira" in State of Alagoas, Brazil. The observations were made with ten pairs of adult insects reared in laboratory on pieces of palma infested with scales which were renewed every 48 hours. The temperature was kept at 25°C ± 5°C, relative humidity at 80% ± 10% and photophase of twelve hours. The life cycle this specie was 21,54 days for the males and 21,31 days for the females. The incubation period was 4,88 ± 0,11 days, and the larvae with four instar, was 11,30 ± 0,11 days. The female lays an average of 305,60 ± 58,51 eggs in an oviposition period of 45,90 ± 6,61 days, with an maximum of 29 eggs per day. A longevity of 128,13 ± 20,08 days for the male and of 122,63 ± 14,33 days for the female was recorded. In the laboratory the technique developed for rearing Curinus sp. on its host D. echinocacti was efficient and it could be used in biological control program.